Evaluating the environmental microbiota across four National Health Service hospitals within England. (January 2023) - Watson, F.; Wilks, S.A.; Keevil, C.W.; Chewins, J.
Summary: Hospital surfaces contaminated with microbial soiling, such as dry surface biofilms (DSBs), can act as a reservoir for pathogenic micro-organisms, and inhibit their detection and removal during routine cleaning. Studies have recognized that such increases in bioburden can hinder the impact of disinfectants and mask the detection of potential pathogens. Cleanliness within healthcare settings is often determined through routine culture-based analysis, whereby surfaces that exhibit >2.5 colony-forming units (CFU) per cm 2 pose a risk to patient health; therefore, any underestimation could have detrimental effects. This study quantified microbial growth on high-touch surfaces in four hospitals in England over 19 months. This was achieved using environmental swabs to sample a variety of surfaces within close proximity of the patient, and plating these on to non-specific low nutrient detection agar. The presence of DSBs on surfaces physically removed from the environment was confirmed using real-time imaging through episcopic differential interference contrast microscopy combined with epifluorescence. Approximately two-thirds of surfaces tested exceeded the limit for cleanliness (median 2230 CFU/cm 2 ), whilst 83% of surfaces imaged with Bac Light LIVE/DEAD staining confirmed traces of biofilm. Differences in infection control methods, such as choice of surface disinfectants and cleaning personnel, were not reflected in the microbial variation observed and resulting risk to patients. This highlights a potential limitation in the effectiveness of the current standards for all hospital cleaning, and further development using representative clinical data is required to overcome this limitation.